2016
DOI: 10.18860/jia.v4i2.3487
|View full text |Cite
|
Sign up to set email alerts
|

A Document of Ibadi Fiqh Governing the Architecture of Mosques

Abstract: In spite of a long-standing interest in the Ibadi community and its historical, social, religious and architectural legacy, its Ibadi scholarly literature remains largely unknown. The present research continues in the footsteps of the pioneering works of Joseph Schacht (Schacht, 1954) and Pierre Cuperly (Cuperly, 1988) on Ibadism. It aims to cast light on the Ibadi literature that represents an authentic source of information for the study of Ibadism past and present. This article analyzes an Ibadi manuscript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…As mentioned in earlier research, this whole practice of Mihrab decoration is not "encouraged" in the Ibadhi jurisprudence related to the mosque architecture (Benkari-Boudidah, 2014;Benkari, 2016Benkari, , p. 60, 2019. But it seems that such practices were tolerated in some regions of Oman (Benkari, 2016). However, this tolerance was not the same everywhere and always.…”
Section: -The Decoration With Embedded "Chinese" Ceramic Platesmentioning
confidence: 96%
See 3 more Smart Citations
“…As mentioned in earlier research, this whole practice of Mihrab decoration is not "encouraged" in the Ibadhi jurisprudence related to the mosque architecture (Benkari-Boudidah, 2014;Benkari, 2016Benkari, , p. 60, 2019. But it seems that such practices were tolerated in some regions of Oman (Benkari, 2016). However, this tolerance was not the same everywhere and always.…”
Section: -The Decoration With Embedded "Chinese" Ceramic Platesmentioning
confidence: 96%
“…Moreover, due to the limitation of the publication length, it was not possible to further develop the understanding of the social and professional networks that prevailed in the production of these Mihrabs. Further research is also needed to discuss the practice of Mihrab decoration with figurative images in the light of the Ibadi jurisprudence which clearly prohibits any ornamentation in the construction, especially in the Qibla wall (Benkari, 2016). Finally, this research also opens the opportunity to further explore the practical integration of the identified style and typology in the Mihrab decoration in Oman or the region.…”
Section: Editorial Universitat Politècnica De Valènciamentioning
confidence: 97%
See 2 more Smart Citations
“…Second, the same local materials and construction techniques that the Omanis use for their residential buildings were used in these forts and palaces. Finally, as the Ibadi religious rules required, there was no excess in the size or ornamentation of the forts and palaces built by Al-Ya'ariba [67]. Therefore, it made it possible for the Omanis to use their architectural language in their buildings.…”
Section: The Prevalence Of Al-ya'arubi Military Architectural Forms I...mentioning
confidence: 99%